(untitled) (Bangladesh Journal of Agricultural Research, 2011)
A socio-economic study was carried out in two rice production environments (Gazipur and Tangail) to assess the comparative advantages of using urea super granule (USG) over prilled urea (PU) in modern rice production and to examine the differences in producers’ technical efficiency between USG user and non- user in crop management. Stochastic frontier production model was employed to examine the farm specific technical efficiency difference in crop management between USG and PU users in the study areas. Analysis revealed that comparatively low amount (36%) of urea was needed in modern boro rice production using USG instead of PU. Nearly 366 % more labour was needed in the USG using plots compared to that of PU user plots, while weeding cost was a bit lower in USG using plots. Analysis also indicated that the sample farmers were able to achieve additional yield of 0.87 t/ha by using USG and this yield gain further resulted to additional benefit of Tk. 11506/ha. For the resource poor rice farms, this benefit is considered to be substantive. Farmers’ contact with the technology disseminators, training on rice production and the use of USG (instead of PU) were the important factors of increasing rice farmers’ technical efficiency in crop management and productivity enhancement as well. According to the farmers’ opinion, there were several constraints in using USG and out of those, requirement of more labour and non availability of USG in proper time were the dominant ones. Keywords: Urea super granule; prilled urea; flood-prone ecosystem; technical efficiency; productivity. DOI: http://dx.doi.org/10.3329/bjar.v36i1.9237 BJAR 2011; 36(1): 129-141